STUDENTS’ POLITENESS STRATEGIES IN ONLINE LEARNING CLASSROOM - Irma Fitriani; Tofan Dwi Hardjanto (Journal of Linguistic Phenomena (JLP), 2023)
In recent years, online learning platforms have grown rapidly and become one of the most common choices in the world. This study aims to reveal the politeness strategies chosen by students in the international online classroom with multicultural students in different countries. The interaction mostly happens on teacher-student discussion, peer-to-student feedback, and individual and class discussions in which the communication is based on writing format. This study uses a qualitative descriptive method and uses the theory of politeness from Brown and Levinson. The research results revealed that the most widely used strategies were positive politeness strategies (49%), negative politeness strategies (35%), off record strategies (8%), and bald-on record strategies (8%). The major factors that influence the use of these strategies are training and learning contracts that begin before class.